A First Report on Multidrug-Resistant Escherichia coli O25 ST131 Dissemination in an Outpatient Population in Zagreb, Croatia - Maja Anušić; Tatjana Marijan; Ana Mlinarić Džepina; Vladimira Tičić; Lucija Gršković; Jasmina Vraneš (Antibiotics)
Background/Objectives: Antimicrobial resistance of the E. coli O25 ST131 clonal lineage poses a significant therapeutic challenge worldwide, often involving resistance to fluoroquinolones and extended-spectrum beta-lactamase (ESBL) production. This retrospective study compared the dissemination of multidrug-resistant E. coli O25 ST131 isolated from the urine of outpatients at the largest Croatian clinical microbiology department across six years over two study periods. Methods: The E. coli O25 ST131 clonal lineage was detected via a rapid PCR method using pabB and trpA primers after positive agglutination with E. coli serogroup O25 antisera. ESBL phenotypes and antibiotic susceptibility were investigated according to EUCAST guidelines and breakpoint tables. Results: In the first period, there were a total of 45 isolates of E. coli O25 ST131, among which 30 were isolates with proven ESBL production. In the second period, a total of 114 isolates of E. coli O25 ST131 were detected, among which 75 (65.8%) were ESBL-positive (p > 0.05). In ESBL-negative strains, the multidrug-resistant (MDR) phenotype was characterized by simultaneous resistance to ampicillin, co-trimoxazole, and fluoroquinolones (with an equal proportion of 3/15 isolates in the first period and 7/39 isolates in the second period, p > 0.05). There was no statistically significant difference in the frequency of MDR detection across the two study periods (36/45 and 98/114, p > 0.05). This is the first detection of E. coli O25 ST131 in the outpatient population in Zagreb. Conclusions: There was no statistically significant difference in the frequency of detecting the E. coli O25 ST 131 clone across the two study periods. The high frequency of MDR phenotype among ESBL-negative isolates of E. coli O25 ST131 and an equally high proportion of MDR strains among ESBL producers in this clonal lineage, with the total detection of MDR isolates ≥ 80% in both study periods, are the reasons why this bacterial clone poses a public health threat and why further investigation into its metabolic and virulence characteristics is needed in order to estimate its spreading potential among the outpatient population in Zagreb.